Deportability, Deportation and Nigerian 'Deportspora' in China - Adebayo, Kudus Oluwatoyin (African Human Mobility Review, 2023)
How do the manifestations of deportability in everyday life and deportation experiences constitute African migrants into a “deportspora” in China? Despite the scholarly attention paid to the migration of Africans to China, questions of deportability and the simultaneous, reverse flows through their deportation are under-explored. In this article, I examine this critical gap by exploring the lifeworlds of Nigerian migrants and deportees from China, using data from two separate studies conducted in 2017 and 2020–2021. Nigerians are exposed to “illegalization,” experience deportability threats, and become vulnerable to arrest and re-dispersal as deportees. The realities of being undocumented and overstaying, the social act of running, and the host society’s instrumentalization of deportation to regulate or order the migrant community all point to the existence of Nigerian deportspora in China. The import of this form of social formation makes deportability and deportation an essential part of social life in the African migrant community in the Chinese city of Guangzhou. The article advances critical debates in deportation studies, especially in the under-researched context of Sino-African migrations.